(untitled) - Hieronymi, Otto (Houndmills, Basingstoke, Hampshire, 1987)
Today the influence of technology is pervasive in virtually all aspects of official relations among States and in the complex web of private cross-border relations. The development, the diffusion and the use of technology deeply affect issues of peace and war, pverty and economic growth, questions of health and disease, the de-terioration and the protection of the environment, as well as intellectual and cultural developments and ultimately the future of the free society...
Keywords: Quan hệ kinh tế quốc tế,International relations,International economic relations,Quan hệ quốc tế